Appropriate Audit Support System Use: The Influence of Auditor, Audit Team, and Firm Factors - Dowling, Carlin (The Accounting Review, 2009)
ABSTRACT: I use Adaptive Structuration Theory (DeSanctis and Poole 1994) and the Theory of Planned Behavior (Ajzen 1991) to model the factors influencing whether auditors use audit support systems appropriately. Understanding the factors that influence appropriate use is important for audit firms to achieve efficient and effective audits from deploying audit support systems. Using a unique data set obtained from 569 auditors, I provide evidence that intention to use the system appropriately and external control increase appropriate use. I find that audit support system restrictiveness and the effectiveness of the audit review process are antecedents of external control. Team and firm consensus on appropriation are antecedents of perceived normative pressure, which, along with an auditor's attitude and self-efficacy, influence an auditor's intention to use the system appropriately. The model is relatively stable across different audit support system designs, but differences are evident across the audit team hierarchy.